EVALUATING THE EFFECTIVENESS OF THE BUSUU APPLICATION IN ENHANCING ENGLISH VOCABULARY ACQUISITION - Pardede, Nurlianti; Putri, Aulia (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2024)
The purpose of this research was to determine the impact of the Busuu application on students' English vocabulary acquisition. The study population consisted of all seventh-grade students at SMPN 30 BATAM, totaling 430 students across ten classes. A random cluster sampling technique was employed to select 76 students, with 38 students in the experimental group and 38 in the control group. Data collection involved a pre-test and post-test, with validity ensured through established testing procedures. The data were analyzed using a t-test, with normality and homogeneity verified via the Kolmogorov-Smirnov test and the F-test, respectively. The experimental group received instruction using the Busuu application, while the control group did not. The analysis revealed that the significance value (sig. 2-tailed) was less than 0.05 (0.000 < 0.05), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). This indicates a significant effect of using the Busuu application on students' English vocabulary acquisition. Despite these findings, the study suggests that the Busuu application could still be a valuable tool for enhancing students' vocabulary knowledge.